2005
DOI: 10.1016/j.rapm.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Intrathecally Administered Bupivacaine Involves the Posterior Roots/Posterior White Matter and Is Milder Than Lidocaine in Rats

Abstract: The neurotoxic lesions caused by bupivacaine and lidocaine were indistinguishable in the primary site and the extending pattern, such as axonal degeneration originating from the posterior roots and extending to the posterior white matter. The intrathecal neurotoxicity is greater in lidocaine than in bupivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…After recovery from surgery, verification of chronically implanted lumbar catheters was determined by observing temporary hindlimb paralysis resulting from an intrathecal injection of 20 l (0.5%) of xylocaine-MPF. No histological abnormalities are produced after single lumbar intrathecal injections of 2% lidocaine or 0.5% bupivacaine (0.12 l/g body weight) in the rat (Takenami et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
“…After recovery from surgery, verification of chronically implanted lumbar catheters was determined by observing temporary hindlimb paralysis resulting from an intrathecal injection of 20 l (0.5%) of xylocaine-MPF. No histological abnormalities are produced after single lumbar intrathecal injections of 2% lidocaine or 0.5% bupivacaine (0.12 l/g body weight) in the rat (Takenami et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
“…In our previous study using the same protocol, we reported the induction of histological lesions by bupivacaine, mepivacaine, and prilocaine (each at eight times), 11 lidocaine (3.7 times), 9 and tetracaine (four times) 10 higher than their clinical respective concentrations. In the present study, the concentration experiment indicated that procaine, levobupivacaine, and ropivacaine did not induce lesions even when used at ten times the clinical concentrations, suggesting that these three agents are less toxic than the drugs tested previously.…”
Section: Discussionmentioning
confidence: 93%
“…bupivacaine for the central nervous and cardiovascular systems in animals 4,5 and humans. [6][7][8] In a series of studies, we determined the neurotoxicities of lidocaine, tetracaine, bupivacaine, mepivacaine, prilocaine, and procaine [9][10][11][12] in a rat spinal model. These studies showed that all these agents, with the exception of procaine, were neurotoxic, with lesions displaying common features irrespective of the anesthetic agent and affecting mainly axons of the dorsal root entry zone.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…; on the other hand, its disadvantages are the following: Its application requires time and expertise; there is application error related post interventional risk of neurological sequels; local anesthetic toxicity; technique related complications; and vets' lack of adequate knowledge 2,7,8, 13 . It has been stated that complications such as hypotension, bradycardia, vomiting, cardiac failure, meningitis and meningismus, paralysis, urinary retention and the cauda equina syndrome can be seldom manifested following the application of spinal anesthesia .…”
Section: 8-13mentioning
confidence: 99%